2002
DOI: 10.2134/jeq2002.2074
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Microbial Communities and Organic Malodor Indicator Compound Concentrations in Various Types of Swine Manure Storage Systems

Abstract: Anaerobic manure storage systems are one of the major contributors to the odor and environmental pollution associated with swine (Sus scrofa) production systems. The microbial ecology of manure storage systems and the relationships between microbial communities and odor production are largely unknown. In this study, we used community fatty acid methyl ester (FAME) analysis to generate lipid profiles to assess seasonal differences among microbial communities inhabiting various types of outdoor swine manure stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
1
10
2
Order By: Relevance
“…2c), an observation also reported by Lovanh et al (2009) for an anaerobic lagoon in Kentucky. Although seasonal temperature ranges may differ from those reported for lagoons in other regions of the USA, the seasonal pattern reported in the present study is similar to those reported for swine lagoons in Iowa (Merrill and Halverson, 2002), Kansas (DeSutter and Ham, 2005), Kentucky (Cook et al, 2010), and North Carolina (Vanotti and Szogi, 2008). Correlations between air and lagoon temperatures and emissions of ammonia, greenhouse gasses, and malodorants have been widely studied, and it is generally agreed that lagoon water temperature is a significant factor in volatilization processes (Harper et al, 2000;DeSutter and Ham, 2005;Aneja et al, 2008;Blunden and Aneja, 2008;Blanes-Vidal et al, 2010;Loughrin et al, 2011).…”
Section: Environmental Factorssupporting
confidence: 76%
“…2c), an observation also reported by Lovanh et al (2009) for an anaerobic lagoon in Kentucky. Although seasonal temperature ranges may differ from those reported for lagoons in other regions of the USA, the seasonal pattern reported in the present study is similar to those reported for swine lagoons in Iowa (Merrill and Halverson, 2002), Kansas (DeSutter and Ham, 2005), Kentucky (Cook et al, 2010), and North Carolina (Vanotti and Szogi, 2008). Correlations between air and lagoon temperatures and emissions of ammonia, greenhouse gasses, and malodorants have been widely studied, and it is generally agreed that lagoon water temperature is a significant factor in volatilization processes (Harper et al, 2000;DeSutter and Ham, 2005;Aneja et al, 2008;Blunden and Aneja, 2008;Blanes-Vidal et al, 2010;Loughrin et al, 2011).…”
Section: Environmental Factorssupporting
confidence: 76%
“…As known, odors are a complex mixture of VFAs, phenolic and indolic compounds, amides, and sulfides (Zahn et al, 1997; Williams et al, 1981; Conn et al, 2007); therefore, it is not very accurate to choose one or two odorants as indicators of odors from pig manure. In this study, it was not confirmed that a significant decrease in the concentration of phenolic compounds was directly related to the decrease in odor intensity, but phenolic compounds were found to be the possible indicators of microbial community changes in pig manure storage systems (Merrill et al, 2002). NH 3 and H 2 S are not always the sensitive components in the odor from livestock manure, but they are tremendously hazardous (Heber et al, 2002;Schiffman et al, 2001); consequently, they are always used as important evaluating indicators for livestock manure odor.…”
Section: Resultscontrasting
confidence: 69%
“…The problem of malodor is an important issue, and some investigations have been performed on the microbial community related to malodor emission in various types of biowastes (Merrill and Halverson 2002; Mayrhofer et al. 2006).…”
Section: Discussionmentioning
confidence: 99%